The Predictability of Chinese English as a Foreign Language Students’ Willingness to Communicate Through Teachers’ Immediacy and Teacher–Student Rapport - Cai, Manyuan (Frontiers in Psychology, 2021)
The teacher–learner relationship is not just a simple action and reaction on both sides of the relationship but a complete exchange that takes shape in the context of the factors that affect it. To understand the factors affecting this relationship, the present study investigated the predictability of Chinese English as a Foreign Language (EFL) students’ willingness to communicate (WTC) through teachers’ immediacy and teacher–student rapport. To conduct the study, 858 EFL students from Xinyang Normal University in Henan province of China were invited to participate in the study. To collect the required data, the researcher employed the Willingness to Communicate Questionnaire, Verbal and Nonverbal Immediacy Questionnaire, and Professor–Student Rapport Scale. Pearson product–moment correlation coefficient and structural equation modeling (SEM) were used to analyze the data. Results revealed that there was a strong positive relationship between teacher immediacy and teacher–student rapport and learners’ willingness to communicate. The findings also demonstrated that teachers’ immediacy and teacher–student rapport were positive predictors of learners’ willingness to communicate. The paper argues that teachers need to enhance their interpersonal relations with their students to make them willing to communicate in their classes.